Pemanfaatan Limbah Eceng Gondok Sebagai Energi Biogas Dengan Menggunakan Digester - Herman Nawir; Muhammad Ruswandi Djalal; Apollo Apollo (Muhammadiyah University, Sidoarjo, 2018)
Biogas is an alternative energy in the form of gas formed from the process of fermentation of organic materials. One of the most abundant organic materials is water hyacinth. This research aims to design the tool that will be used to process water hyacinth so that it can produce biogas energy. The main components of the equipment made consist of digester, water trap, gas container, and gas stove, each made 3 appliances. The experiment was conducted using 3 pieces of digester where each digester was filled with 10kg of water hyacinth and different starter. Digester A uses a 0.5 liter EM4 starter mixed with 4.5 liters of water. Digester B using starter 5 kg of cow dung mixed with water 3 liters. And digester C using starter 5 kg of cow dung mixed with 0.5 liters EM4 and 4, 5 liters of water. Then see the development of biogas during the fermentation process (35 days). From the results of this study can be obtained biogas pressure, temperature, acidity (pH) and the duration of the flame generated by the means of producing biogas using this digester and can be applied to the stove. The pressure change produced by digester C is greater than the pressure generated from digesters A and B. The temperature changes produced in digester C are greater than the temperature produced by digesters A and B. The initial pH value of mixing for digester A is pH 6.3, digester B with pH 7.5 and digester C with pH 5.5. The pH value after biogas was produced for digester A with pH 7.5, digester B with pH 7.5 and digester C with pH 7.6. This corresponds to a good pH for the growth of biogas-forming microbes, ranging from 6.4 to 7.8. The fire generated on the blue flame test, with the total length of the flame for each digester is 54 minutes 46 seconds.